2011
DOI: 10.1016/j.ijbiomac.2011.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of angiotensin converting enzyme 2 (ACE2) from murine model of mesangial cell in culture

Abstract: Angiotensin converting enzyme 2 (ACE2) is a component of the renin-angiotensin system (RAS) which converts Ang II, a potent vasoconstrictor peptide into Ang 1-7, a vasodilator peptide which may act as a negative feedback hormone to the actions of Ang II. The discovery of this enzyme added a new level of complexity to this system. The mesangial cells (MC) have multiple functions in glomerular physiology and pathophysiology and are able to express all components of the RAS. Despite of being localized in these ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 30 publications
2
18
0
3
Order By: Relevance
“…Furthermore, expression of ACE2 was reported in human aortic endothelial cells in culture (20). Therefore, GEnCs could be an additional source of glomerular ACE2, along with podocytes (58, 63) and mesangial cells (2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, expression of ACE2 was reported in human aortic endothelial cells in culture (20). Therefore, GEnCs could be an additional source of glomerular ACE2, along with podocytes (58, 63) and mesangial cells (2).…”
Section: Discussionmentioning
confidence: 99%
“…After a 1-h starvation period, cells were maintained in serum-free medium and spiked with 1 M ANG I [ANG- (1)(2)(3)(4)(5)(6)(7)(8)(9)(10) the addition of the ANG substrate. Conditioned media were collected at various time points and stored at Ϫ20°C until assayed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the kidney, ACE2 is present in podocytes, mesangial cells, parietal epithelium of Bowman's capsule, proximal cell brush border, and collecting ducts (3,32,40,84). Several models of nephropathy have shown that ACE2 is implicated in reducing glomerular and tubular damage as well as fibrosis (43,48,63,84).…”
Section: Ace2: Physiology and Distributionmentioning
confidence: 99%
“…Nevertheless, the angiotensinconverting enzyme 2 (ACE2) was identified as being homologous to ACE but responsible for cleaving ANG II into ANG (1-7), which presents anti-proliferative and vasodilator effects. Thus, the balance between ANG II and ANG (1-7) levels is important for controlling RAS activity (2,9,14,15,23,28,33).…”
mentioning
confidence: 99%